Analisis Pengaruh Rasio Kemandirian Keuangan Daerah dan Pertumbuhan Ekonomi Terhadap Indeks Pembangunan Manusia Di Kabupaten Tanah Bumbu, Kotabaru dan Tanah Laut Periode (2010-2020) - Rosita, Rosita; Muzdalifah, Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The purpose of this study is to analyze how the Regional Financial Independence Ratio, Economic Growth, and Human Development index of Tanah Bumbu, Kotabaru, and Tanah Laut have an effect on the Tanah Bumbu, Kotabaru, and Tanah Laut and analyze how the Economic Growth affects the Human Development Index in of Tanah Bumbu, Kotabaru, and Tanah Laut. This study uses regional financial independence, linear panel data regression, classical assumption test, and hypothesis testing. The results of this study indicate that the ratio of regional financial independence partially has a significant adverse effect on the Human Development Index (HDI); the test results show that the probability count is 0.0549>0.05. Meanwhile, economic growth partially has a significant positive effect on the human development index (HDI). The test results show that the probability value of count is 0.0033<0.05.